2013 IEEE Global Communications Conference (GLOBECOM) 2013
DOI: 10.1109/glocom.2013.6831134
|View full text |Cite
|
Sign up to set email alerts
|

An empirical performance study of Intra-vehicular Wireless Sensor Networks under WiFi and Bluetooth interference

Abstract: Abstract-Intra-Vehicular

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…They enhanced the performance of BLE to guarantee a worst-case latency required by automotive systems. Similarly, Lin et al [12] evaluated the impact of in-vehicle interference caused by the simultaneous use of different ISM band wireless technologies. They concluded that BLE is the most resilient technology when it comes to interference.…”
Section: Related Workmentioning
confidence: 99%
“…They enhanced the performance of BLE to guarantee a worst-case latency required by automotive systems. Similarly, Lin et al [12] evaluated the impact of in-vehicle interference caused by the simultaneous use of different ISM band wireless technologies. They concluded that BLE is the most resilient technology when it comes to interference.…”
Section: Related Workmentioning
confidence: 99%
“…There are many sensors in a vehicle such as the engine and drive control [1,2,3]. The power is transferred to the sensors and the engine control unit using a wire harness.…”
Section: Introductionmentioning
confidence: 99%